Penerapan Model Pembelajaran Project Based Learning (PjBL) dalam Meningkatkan Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 13 Mataram Tahun Pelajaran 2023/2024 - Padmi, Ni Ayu Putu (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This Classroom Action Research (CAR) aims to improve student learning outcomes through the application of the Project Based Learning (PjBL) learning model. The research was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The results of the study showed that in cycle I, the percentage of students who scored 75 or more was 35%. This shows that the research indicators have not reached the classical completion standard of 75%, because there are still 9 students who have not achieved learning completion. In cycle II, an average score of 81.3 was obtained with the highest score of 90 and the lowest score of 75. The number of students who achieved learning completion was 14 people, or 100% of the total students, so that it has exceeded the minimum classical completion limit of 75%. These results indicate that there has been a significant increase compared to the initial conditions. With all students having achieved learning completion, it can be concluded that the actions taken in this study were effective and succeeded in improving student learning outcomes. Therefore, this Classroom Action Research (CAR) is declared complete at the end of cycle II.